2021
DOI: 10.1063/5.0068032
|View full text |Cite
|
Sign up to set email alerts
|

Fractal-like photonic lattices and localized states arising from singular and nonsingular flatbands

Abstract: We experimentally realize fractal-like photonic lattices by use of the cw-laser-writing technique, thereby observing distinct compact localized states (CLSs) associated with different flatbands in the same lattice setting. Such triangle-shaped lattices, akin to the first generation Sierpinski lattices, possess a band structure where singular non-degenerate and nonsingular degenerate flatbands coexist. By proper phase modulation of an input excitation beam, we demonstrate not only the simplest CLSs but also the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…[17] Only recently first efforts were made to combine the two classes of flat bands in an optically induced lattice in a photorefractive crystal. [18] However, up to now, no experimental realization has proved the coexistence of these two topological classes of Singular and nonsingular flat bands in a Sierpinski fractal-like photonic lattice are reported. It is demonstrated that the lowest two bands, being isolated and degenerate due to geometrical frustration, are nonsingular and thus can be spanned by a complete set of compact localized states.…”
Section: Localized States Emerging From Singular and Nonsingular Flat...mentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Only recently first efforts were made to combine the two classes of flat bands in an optically induced lattice in a photorefractive crystal. [18] However, up to now, no experimental realization has proved the coexistence of these two topological classes of Singular and nonsingular flat bands in a Sierpinski fractal-like photonic lattice are reported. It is demonstrated that the lowest two bands, being isolated and degenerate due to geometrical frustration, are nonsingular and thus can be spanned by a complete set of compact localized states.…”
Section: Localized States Emerging From Singular and Nonsingular Flat...mentioning
confidence: 99%
“…[ 17 ] Only recently first efforts were made to combine the two classes of flat bands in an optically induced lattice in a photorefractive crystal. [ 18 ] However, up to now, no experimental realization has proved the coexistence of these two topological classes of singular and nonsingular flat bands in a single lattice by analyzing the completeness conditions of the sets of CLSs. Here, we propose and experimentally demonstrate, for the first time to our knowledge, a fractal‐like lattice that exhibits multiple flat bands fabricated by femtosecond direct laser writing on a large‐scale fused silica chip.…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of the decimation method to understand the fundamental character of single particle excitations in several other lattice models, including geometric fractal networks, will also be discussed. The latter systems, that is, the fractal networks, have recently been experimentally realized 7 and thus a comprehensive study of their properties, especially with regard to the exact evaluation of the compact localized eigenstates and topological orders in fractals, 8 is very important, to our mind.…”
Section: Introductionmentioning
confidence: 99%
“…This works easily when the unit cell has simple geometry, but turns out to be a tedious job in cases where the unit cell has an intricate internal structure. This issue has become pertinent and needs to be addressed, in particular, after a series of fascinating experiments reported laboratory realizations of the classic Sierpinski gasket fractal (SGF) [23][24][25] and observation of CLS [26][27][28][29][30] and photonic Floquet topological phase 31 on engineered SGF substrates. The latter experiments were done on SGF structures grafted either mainly by the femtosecond laser writing techniques, or designed with evanescently coupled helical waveguides, for example.…”
Section: Introductionmentioning
confidence: 99%